2021
DOI: 10.3389/fphar.2021.682520
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor Blockade Protects Against Acrolein-Induced Bladder Damage: A Potential New Therapeutic Approach for the Treatment of Bladder Inflammatory Diseases

Abstract: Inflammatory conditions of the urinary bladder have been shown to be associated with urothelial damage and loss of function. The purinergic P2X7 receptor has been implicated in several inflammatory conditions. The aim of this study was to investigate the role of the P2X7 receptor in acrolein-induced inflammatory damage using the porcine urinary bladder. For this purpose, an ex-vivo model of porcine urothelial damage induced by direct instillation of acrolein into the whole bladder lumen was used. To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 93 publications
(112 reference statements)
1
2
0
Order By: Relevance
“…These changes, which are analogous to the changes seen in patients with interstitial cystitis, were inhibited by pre-treatment of urothelial cells with P2X7R antagonist, A804598. These findings are in line with our previously reported observations in our ex-vivo model of urothelial damage by direct instillation of acrolein into the whole porcine bladder lumen ( Taidi et al, 2021 ) and provide further evidence for the potential of P2X7R antagonists in the treatment of IC/PBS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These changes, which are analogous to the changes seen in patients with interstitial cystitis, were inhibited by pre-treatment of urothelial cells with P2X7R antagonist, A804598. These findings are in line with our previously reported observations in our ex-vivo model of urothelial damage by direct instillation of acrolein into the whole porcine bladder lumen ( Taidi et al, 2021 ) and provide further evidence for the potential of P2X7R antagonists in the treatment of IC/PBS.…”
Section: Discussionsupporting
confidence: 92%
“…Using an ex-vivo porcine bladder model, we have recently reported that instillation of acrolein into the bladder lumen caused damage to the urothelial and suburothelial layers, along with diminished bladder contractility in response to acetylcholine stimulation. The addition of P2X7R antagonist significantly attenuated acrolein-induced damage to the bladder ( Taidi et al, 2021 ). The aim of this study was to further investigate whether the P2X7R is involved in acrolein-induced changes in urothelial barrier structure and integrity at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…As the cytosolic concentrations of ATP are 1–5 mM [ 41 , 42 ], it is conceivable that ATP released through exocytosis or through PANX1 channels in close proximity with P2X7R can transiently reach effective concentrations to activate this receptor. Like PANX1, P2X7R plays a role in activating and sustaining inflammation and has been implicated in several inflammatory and autoimmune diseases and cancer [ 43 , 44 ], including in the inflammatory processes of animal models of cyclophosphamide or acrolein-induced cystitis [ 45 , 46 ]. It was initially proposed that activation of P2X7R permeabilizes cells to large molecules, such as nucleotides, through gradual dilation of its own channel pore [ 38 , 47 ], or via interaction with other channel-forming proteins (e.g., PANX1) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%